2015
DOI: 10.1096/fj.15-279091
|View full text |Cite|
|
Sign up to set email alerts
|

The higher level of complexity of K‐Ras4B activation at the membrane

Abstract: Is nucleotide exchange sufficient to activate K-Ras4B? To signal, oncogenic rat sarcoma (Ras) anchors in the membrane and recruits effectors by exposing its effector lobe. With the use of NMR and molecular dynamics (MD) simulations, we observed that in solution, farnesylated guanosine 59-diphosphate (GDP)-bound KRas4B is predominantly autoinhibited by its hypervariable region (HVR), whereas the GTP-bound state favors an activated, HVR-released state. On the anionic membrane, the catalytic domain adopts multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
114
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(124 citation statements)
references
References 60 publications
(74 reference statements)
8
114
0
Order By: Relevance
“…However, these drugs were less than successful in human clinical trials [28]. Recently, GTP-bound K-Ras4B was shown to exist in active and inactive state at the membrane, which implies that GDP/GTP exchange may not be sufficient for activating Ras signaling [29]. This result suggests that the mechanism of activating Ras at the membrane has a higher level of complexity than expected.…”
Section: Targeting Ras Based On the Current Signaling Pathwaymentioning
confidence: 99%
“…However, these drugs were less than successful in human clinical trials [28]. Recently, GTP-bound K-Ras4B was shown to exist in active and inactive state at the membrane, which implies that GDP/GTP exchange may not be sufficient for activating Ras signaling [29]. This result suggests that the mechanism of activating Ras at the membrane has a higher level of complexity than expected.…”
Section: Targeting Ras Based On the Current Signaling Pathwaymentioning
confidence: 99%
“…The autoinhibition is released when the catalytic domain is GTP-bound. At the membrane, the HVR autoinhibition persists in the inactive state, blocking the effector-binding site, whereas, in the active state, the catalytic domain is released and fluctuates reinlessly, exposing the effector-binding site [40]. MD simulations supported by NMR data suggested that oncogenic GDP-and GTP-bound KRas4B shift the equilibrium towards such an effector-bindingsite-exposed state [43].…”
Section: Introductionmentioning
confidence: 99%
“…K-Ras favours association with non-raft regions [8,33,34], whereas H-Ras can be found in both lipid raft and non-raft regions [35][36][37][38]. The different affinities of the Ras isoforms to the membrane are mainly due to their posttranslationally modified HVRs [39], which influence the orientations of the Ras-membrane associations [40]. Since the HVRs mainly act in membrane attachment, Ras proteins can form a dimer through the interactions between their catalytic domains.…”
Section: Introductionmentioning
confidence: 99%
“…G12 is the most frequently mutated residue (89%), which most prevalently mutates to aspartate (G12D, 36%) followed by valine (G12V, 23%) and cysteine (G12C, 14%) 3,10 . This residue is located at the protein active site, which consists of a phosphate binding loop (P-loop, residues 10-17) and switch I (SI, residues [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] and II (SII, residues 60-74) regions. The active site residues are bound to the phosphate groups of GTP and are responsible for the GTPase function of K-Ras.…”
Section: Introductionmentioning
confidence: 99%
“…Although the effects of G12D mutation on the structure, conformation and flexibility of K-Ras have been studied [21][22][23][24] , the relationship between its conformational and dynamical changes still remains to be understood. At the same time, there is increasing evidence that suggests that crystal structure studies alone may miss drugbinding pockets on mutant K-Ras surface 18,[25][26][27][28][29][30][31][32][33] . Studies that include dynamics information have recently achieved promising results, however, these are limited to K-Ras G12C mutant, and the mechanisms that regulate its dynamics remain unknown.…”
Section: Introductionmentioning
confidence: 99%